Adsorption of acid green 25 dye solution using modifed and unmodified kenaf fiber - Bagh, Ali Reza Golestan (2015)
Dyes are used widely as coloring in many industries, such as textiles, cosmetics,leather, printing, foods and plastics. Acid dye comprise the largest class of dye in the Color. Acid green 25 in particular belongs to the commercial acid dye often used in textile, hair dye formulation and cosmetic product. The removal of pollutants from wastewaters is a matter of great interest in the field of water pollution. Amongst the numerous techniques of pollutant removal, adsorption is an effective and useful process. In the past few years many approaches have been studied for the development of low cost and effective adsorbents. Kenaf is one of the best natural fibers used as adsorbent in adsorption process. The treatment on natural fibres is widely being used to modified the cellulosic molecular structure. In this study, an attempt is made the chemical modification characteristics of kenaf fiber. In order to enhance the adsorption capacity, kenaf fibers have been treated with sodium hydroxide and trimethylammonium chloride (CHMAC) coupling agent. The charactristics of kenaf fiber was obtained by using Fourier transform infrared ( FTIR),scanning electron microscopy ( SEM) , EDX, BET And CHNS-O and the presence of functional groups such as hydroxyl,amine,lignin and carbonyl group were detected. In this research adsorption of AG 25 dye on modified and unmodifed kenaf consider as a problem statement. The samples was investigated under different pH, dosage of adsorbent, initial dye concentration, contact time and temperature. The un-modified kenaf adsorbed the maximum amount of 107 mg/g of AG25 from aqueous solution at pH of 2, temperature of 30 ○C, contact time of 180 min and dosage adsorbent of 0.8 g/l. At the same condition modifed kenaf adsorbed around 163.94 mg/g of AG25 respectively. According the UV test that was done befor and after adsorption it was found that Separation of AG25 was carried out successfully by using a modified kenaf. Equilibrium isotherms and kinetic models have been measured to assess the capacities of both modify and un-modify kenaf for AG25 for the sorption process. By comparing the correlation coefficients determined for each linear transformation of the isotherm analysis of the study revealed that adsorption behavior was best described by Freundlich model for all modified and unmodified samples. Lagergren-first-order, Pseudo-second-order and Intraparticle diffusion models were applied to determine the kinetics of the adsorption process. Pseudo-second order results showed higher coefficient of determination (R2 >0.99) values compare to the Lagergren-first-order. The adsorption capacity of the kenaf fiber increases with the increase in experimental temperature from 303K to 333K. The negative values of ΔG and positive ΔH obtained indicated that the AG25 dye adsorption process is a spontaneous and an endothermic.Based on the data od present investigation,it was concluded that the modified kenaf fiber can be an effective eco-feiendly and low cost adsorbent to remove acid dye from colored aqueous solution.